2004
DOI: 10.1021/bm049553i
|View full text |Cite
|
Sign up to set email alerts
|

Poly(oxazoline)s with Telechelic Antimicrobial Functions

Abstract: Poly(2-alkyl-1,3-oxazoline)s (alkyl = methyl, ethyl) with terminal quarternary ammonium groups were synthesized. It could be shown by NMR and ESI-MS that the termination of the living polymerization with N,N-dimethylalkyl(butyl to hexadecyl)amines was quantitative. The novel functions were investigated regarding their antimicrobial potential toward the bacterium Staphylococcus aureus revealing that only quarternary ammonium functions with 12 and more carbons are antibacterial. Using a novel bifunctional initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 36 publications
2
109
2
2
Order By: Relevance
“…These examples show the negative effect of PEG on most biocides, which was also found for quarternary ammonium groups attached to the polyether [29]. Interestingly, it was reported that penicillin attached to polyacrylate nanoparticles showed higher activity against Methicillin-resistant Staphylococcus aureus (MRSA) than the free antibiotic in solution [30].…”
Section: Polymeric Biocidesmentioning
confidence: 66%
See 1 more Smart Citation
“…These examples show the negative effect of PEG on most biocides, which was also found for quarternary ammonium groups attached to the polyether [29]. Interestingly, it was reported that penicillin attached to polyacrylate nanoparticles showed higher activity against Methicillin-resistant Staphylococcus aureus (MRSA) than the free antibiotic in solution [30].…”
Section: Polymeric Biocidesmentioning
confidence: 66%
“…One advantage of this polymerization technique is the controlled introduction of a specific group at one end and another group at the distal end of the polymers by choosing a suitable initiator and termination agent. It could be shown that the molecular weight of poly(2-methyl-1,3-oxazolines) (PMOx) and the respective ethyl-derivative (PEtOx) does not influence the activity of the biocidal end group, dimethyldodecylammonium bromide (DDA), in a range of 2,000-10,000 g/mol [29]. Further, a similar derivative containing polyethylene glycol (PEG) showed a 5-10 times lower antimicrobial activity compared to the polyoxazolines.…”
Section: Biocidal Polymersmentioning
confidence: 99%
“…pMeOx and pTMBO [poly(tetramethylene-bis-2-oxazoline)] that were end-capped with N,N-dimethyl-n-dodecylamine showed high antimicrobial activity, whereas linear pEI hydrochloride displayed the lowest minimal inhibitory concentration values, but higher activity against Staphylococcus aureus and Escherichia coli. Tiller and Waschinski initiated the CROP of MeOx and EtOx with the initiator 3-[(tert-butoxycarbonyl)amino]benzyl-p-toluenesulfonate and terminated the polymerizations with tertiary amines exhibiting one long alkyl chain (dimethyl-ndodecylamine and dimethyl-n-hexadecylamine, respectively) [42]. In antimicrobial tests, the authors revealed that the satellite groups of the polymers had great influence on the bioactivity, which was verified with the example of the bacterium Staphylococcus aureus.…”
Section: Telechelic Poly(2-oxazoline)s As Antimicrobially Active Compmentioning
confidence: 91%
“…Other recent studies on structure-property relationships in poly(2-oxazoline)s include their use as compatibilizer, [19] their lower critical solution temperature (LCST), [20,21] micellization behavior, [22] as well as antimicrobial properties. [23,24] However, the generally long polymerization times for 2-oxazolines that range from days to weeks [25,26] represent a major disadvantage that obstructs fast synthesis and screening of libraries of poly(2-oxazoline)s. Therefore, the use of microwave irradiation has been investigated as an alternative heat source for the polymerization of 2-oxazolines. The use of dielectric heating has already resulted in faster and cleaner reactions in a variety of organic syntheses because of the fast and homogeneous noncontact heating, whereby the use of closed reaction conditions provides easy access to high-temperature conditions.…”
Section: Talents and Trendsmentioning
confidence: 99%